2018
DOI: 10.1177/2399808318813576
|View full text |Cite
|
Sign up to set email alerts
|

The definition of syntactic types: The generation, analysis, and sorting of universes of superblock designs

Abstract: Syntactic types are defined as sets of designs with particular properties. We are specifically interested in the definition of deformed grids, a particular type of street network internal to superblocks. The superblocks under study are surrounded by arterial streets and have traversing local main streets and internal street infills. The argument takes advantage of three kinds of rules or algorithms: generative rules that produce a universe of designs, analytical algorithms that can be applied to the descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Increased odds of walking for recreation purposes were associated with increased street network connectivity in certain neighbourhoods with particular characteristics (increased differentiation of connectivity structure). This highlights the significance of planning a dominant foreground structure through the creation of supergrids with traversing local main streets and internal street infills, as argued by Feng and Peponis (2018) and Scoppa et al (2019). On the other hand, no significant association was found between street network connectivity…”
Section: Discussionmentioning
confidence: 88%
“…Increased odds of walking for recreation purposes were associated with increased street network connectivity in certain neighbourhoods with particular characteristics (increased differentiation of connectivity structure). This highlights the significance of planning a dominant foreground structure through the creation of supergrids with traversing local main streets and internal street infills, as argued by Feng and Peponis (2018) and Scoppa et al (2019). On the other hand, no significant association was found between street network connectivity…”
Section: Discussionmentioning
confidence: 88%
“…However, the results of this paper contribute, at this point, to enlarge recent research on superblocks' street networks by including metrics that were not previously discussed, applied, or investigated. Indeed, while syntactic properties of superblocks were recently studied [16,19], and so were route directness, walking sheds, and betweenness centrality [17,18], the evaluation of route distance and diversity add new information to the ongoing research on superblocks. Further, current discussions about the use of superblocks in Chinese cities [62], as well as the study of the adaptation of Cerda's plan in Barcelona to accommodate sustainable mobility modes by aggregating several blocks into superblocks [63,64], highlight the ongoing need to better understand superblocks as a well-established urban planning strategy.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the large number of articles that studied street connectivity as a key component linking urban form to more sustainable transportation modes, not much work has concentrated on superblocks and superblocks-built cities. In fact, with some recent exceptions, few studies addressed the connectivity of these urban street systems, even when constituting a key component in the urbanization strategy of many countries worldwide, and particularly the Middle East [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Zhao et al [38] confirmed that orthogonal street grids with high street density present greater accessibility, while Stahle et al [39] explored the distribution of land uses while addressing physical proximity and Space Syntax. Feng and Peponis [40,41], in turn, explored different street network and grid typologies.…”
Section: Street Network Length As a Proxy For Pedestrian Accessibilit...mentioning
confidence: 99%